If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-4)=5x+10-2
We move all terms to the left:
3(x-4)-(5x+10-2)=0
We add all the numbers together, and all the variables
3(x-4)-(5x+8)=0
We multiply parentheses
3x-(5x+8)-12=0
We get rid of parentheses
3x-5x-8-12=0
We add all the numbers together, and all the variables
-2x-20=0
We move all terms containing x to the left, all other terms to the right
-2x=20
x=20/-2
x=-10
| 6(4x+10)=12 | | ½(5x+12)=2x-3 | | (x/3-7=1 | | 9x+6=3x+12 | | -6(y-5)=4y-10 | | (2x+5)+120+55=360 | | -12=8+e/2 | | 2.5x-8.75=-2 | | v-9=1/7 | | 2(u+3)+1=9 | | 3(x-4)=5x-10-2x | | 14-3(x-5)=2x+4 | | 1x4=4x2 | | -2=x²+6 | | 2x+2x+7/4+1+7/4+1=65 | | 8+5x=4x+7 | | 8x+40=8(1+5x) | | -7p+36=-7(p-5) | | -2(3x+8)=18 | | 2(u-13)+4=12 | | 2.50x15x=1.00x | | -8u+5(u+4)=8 | | 1.5-0.04x=-0.74 | | 7=4x+21 | | 0.3(w+10=1.8w | | (x/10)+4=10 | | 40+4s=100+2s | | M+5(m-7)=-13 | | -x+5=4x-40 | | .5x+.35(30)=26.5 | | 66-x=42 | | 3.5y+8=5.5y-6 |